Modelling Social&Communicative Skills in Children with Special Educational Needs - Germanovna Sigal, Natalya (2021)
The paper covers the issues of theoretical frameworks that are being developing around the process of modelling social communication skills in children with special educational needs during language learning process using interactive teaching techniques. This draws from a wide range of philosophical and psychological works on social and pedagogical rehabilitation of children with special educational needs as one of priority zones in the world policy and educational system aimed at growing attention to widespread acceptance of people with different needs in all spheres of society. Methodology used in the study is theoretical, empirical, methods of collecting data, description and dealing out the outcomes of the research. The study reflects empirical analysis based on observation, interviewing, testing and pedagogical experiment, which took place in the secondary school № 2 of the Republic of Tatarstan, Russia. Innovative ways of engaging social communication in teaching, learning and research led to designing a model for forming social communication skills in children with special educational needs via foreign language learning. The major findings of the research are the created model that makes possible to develop social and communicative skills; implementation of conditions of the development of these skills during pedagogical process; criteria of capacity for development of social and communicative skills of children with special educational needs.